“This is Mordor!” Usytuowanie zjawiska fantastyki w ruchu odtwórstwa historycznego epok starożytności i średniowiecza - Antoszewska, Katarzyna Laura (Instytut Archeolgoii i Etnologii Polskiej Akademii Nauk, 2015)
24 cm Historical reenactment movement seems to be linked to fantasy phenomena in many aspects, however, scientific reflection on this relation is rather small. The article contributes to revealing this question presenting several levels of this relation. Firstly it describes engagement of reenactors in Role-Playing Games (RPG) and Live Action Role-Playing (LARP) and also their active participation in fantasy convents. Secondly it analyses metaphors referring to fantasy used in reenactment to depict historical inaccuracy. Thirdly it shows how beginnings of Polish reenactment movement are rooted in its participants’ fascination with fantasy. Finally the author interprets potential of creating alternative worlds present both in fantasy games and in historical reenactment 24 cm Historical reenactment movement seems to be linked to fantasy phenomena in many aspects, however, scientific reflection on this relation is rather small. The article contributes to revealing this question presenting several levels of this relation. Firstly it describes engagement of reenactors in Role-Playing Games (RPG) and Live Action Role-Playing (LARP) and also their active participation in fantasy convents. Secondly it analyses metaphors referring to fantasy used in reenactment to depict historical inaccuracy. Thirdly it shows how beginnings of Polish reenactment movement are rooted in its participants’ fascination with fantasy. Finally the author interprets potential of creating alternative worlds present both in fantasy games and in historical reenactment